Direct Observation of Magnetic Reconnection Resulting From Interaction Between Magnetic Flux Rope and Magnetic Hole in the Earth's Magnetosheath - Shimou Wang; Rongsheng Wang; Quanming Lu; San Lu; Kai Huang (Geophysical Research Letters)
Abstract We report in situ observation of magnetic reconnection between magnetic flux rope (MFR) and magnetic hole (MH) in the magnetosheath by the Magnetospheric Multiscale mission. The MFR was rooted in the magnetopause and could be generated by magnetopause reconnection therein. A thin current sheet was generated due to the interaction between MFR and MH. The sub‐Alfvénic ion bulk flow and the Hall field were detected inside this thin current sheet, indicating an ongoing reconnection. An elongated electron diffusion region characterized by non‐frozen‐in electrons, magnetic‐to‐particle energy conversion, and crescent‐shaped electron distribution was detected in the reconnection exhaust. The observation provides a mechanism for the dissipation of MFRs and thus opens a new perspective on the evolution of MFRs at the magnetopause. Our work also reveals one potential fate of the MHs in the magnetosheath which could reconnect with the MFRs and further merge into the magnetopause.